Proposta de arquitetura baseada em Internet das Coisas para análise de dados de arboviroses - Tavares, Priscylla da Silva (2018)
With the progress of sensor technologies, there has been an increase in the number of connected computing devices capable of collecting information and interacting with the environment where they are inserted, forming the basis of the Internet of Things (IoT). Such devices enable the development of new applications capable of making cities more intelligent, providing improvements to society and urban infrastructure. As a result of the interaction between different applications, there is a large set of data, from which useful knowledge can be extracted. One recurrent problem of big cities with tropical climate is the occurrence of arbovirus outbreaks (Dengue, Zika and Chikungunya) and there is still a lack of tools and information to help preventing these outbreaks. This research proposes an architecture capable of aggregating data from different types of IoT devices and crowdsourcing, in order to assist the decision making, prevention, and surveillance of arbovirus outbreaks. The architecture validation took place through the exploratory analysis of climatology data, arboviruses cases and sanitation of the city of Fortaleza-CE from 2011 to 2017, as well as the implementation of a prototype of the architecture. Through this procedure, the correlation between the selected data was verified, the influence of the chosen data sources for the epidemics monitoring and prediction of outbreaks was analyzed, and it was also verified that the prototype worked as planned.